Seasonality of canopy invertebrate communities in eucalyptforests of eastern and western Australia - Recher, H.; Majer, Jonathan; Ganesh, S. (1996)
Chemical knockdown procedures were used to sample canopy arthropods at 3 month intervals over 1 year at two sites, one in eastern Australia and the other in western Australia. Samples were taken from narrow-leaved ironbark, Eucalyptus crebra, and grey box, Eucalyptus moluccana, in the east and from jarrah, Eucalyptus marginata, and marri, Eucalyptus calophylla, in the west. Arthropods were more abundant on trees in eastern Australia and exhibited different seasonal patterns from those in the west. Members of different functional groups exhibited different seasonal patterns, with some herbivorous groups responding to times of leaf production, decomposers and fungus feeders responding to high moisture availability, and predators/parasites responding to the abundance of food items. Seasonal variability was slightly higher in the west, possibly reflecting the greater seasonal amplitude in rainfall. In the eastern forest, proportionately more taxa peaked in spring or summer and declined to minimum numbers in winter. In the western forest several taxa attained peak numbers in autumn, winter or spring, while others declined to minimum values in winter or summer. The phenological patterns of canopy arthropods appear to be linked to the condition of the host plant and/or to climatic factors. Comparison of the western Australian data to those from a second year of sampling at a time when rainfall was greater and fell later into the season indicated that variability in arthropod numbers between years can be as great as that between seasons. Implications of the variability in seasonal and annual patterns of canopy invertebrate communities are discussed in relation to the need for long-term sampling and in relation to evaluating the impact of disturbance on forest communities.